2009
DOI: 10.1111/j.1360-0443.2008.02444.x
|View full text |Cite
|
Sign up to set email alerts
|

Computer‐based psychological treatment for comorbid depression and problematic alcohol and/or cannabis use: a randomized controlled trial of clinical efficacy

Abstract: Computer-based treatment, targeting both depression and substance use simultaneously, results in at least equivalent 12-month outcomes relative to a 'live' intervention. For clinicians treating people with comorbid depression and alcohol problems, BIs addressing both issues appear to be an appropriate and efficacious treatment option. Primary care of those with comorbid depression and cannabis use problems could involve computer-based integrated interventions for depression and cannabis use, with brief regular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
253
3
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(264 citation statements)
references
References 28 publications
(26 reference statements)
7
253
3
1
Order By: Relevance
“…Comorbidity treatment guidelines [41] together with evidence from the literature [42] consistently recommend that both addiction and psychiatric approaches are essential to effectively treat people experiencing comorbid addictive and psychiatric disorders. Despite this, only one-third of the people with comorbid AD+AUD sought treatment for both of their disorders, and only 8% of these reported that they receive effective and adequate treatment for both disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comorbidity treatment guidelines [41] together with evidence from the literature [42] consistently recommend that both addiction and psychiatric approaches are essential to effectively treat people experiencing comorbid addictive and psychiatric disorders. Despite this, only one-third of the people with comorbid AD+AUD sought treatment for both of their disorders, and only 8% of these reported that they receive effective and adequate treatment for both disorders.…”
Section: Discussionmentioning
confidence: 99%
“…42] as a potential immediate solution to this problem. For example, recent research has indicated the efficacy of a clinicianassisted computerised treatment program for depression and alcohol/ other drug use problems, with equivalent benefits reported for both depression and alcohol use as an entirely therapist-delivered treatment [42,44]. The Internet (and related technologies) show promise as a means of closing the gap between evidence and clinical practice in this context [42,45,46].…”
Section: Discussionmentioning
confidence: 99%
“…One randomized clinical trial compared the effectiveness of computer versus therapist delivered CBT with MI components [36]. All patients had comorbid depression with substance misuse, a substantial portion of which was alcohol misuse, and each received a single session of integrated CBT/MI before being randomized to a no treatment control condition, or nine sessions of CBT/MI delivered by a psychotherapist or a computer.…”
Section: Treatment Of Co-occurring Depression and Substance Related Pmentioning
confidence: 99%
“…Rollman y cols midieron la efectividad de una intervención telefónica llevada a cabo por enfermeras supervisadas por un psiquiatra en colaboración con médicos de atención primaria de 8 meses de duración dirigido a pacientes con depresión post bypass coronario encontrando que a los 8 meses, la intervención telefónica era más efectiva en relación a la calidad de vida relacionada con la salud mental, a la sintomatología depresiva y a la funcionalidad física en comparación con el manejo usual de estos casos 22 . Kay-Lambkin y cols llevaron a cabo un ECC de tres ramas en pacientes mayores de 16 años depresivos con consumo problemático de alcohol o marihuana quienes fueron aleatorizados luego de recibir una intervención breve (BI) a un grupo control , a un tratamiento de nueve sesiones de orientación cognitiva conductual persona a persona o computarizada con apoyo breve pero semanal persona a persona encontrando que el grupo control tiene resultados desfavorables en comparación con las dos intervenciones y que, a los 12 meses de seguimiento, ambas intervenciones fueron equivalentes en disminuir la sintomatología depresiva y el uso de substancias ahorrando la intervención computarizada tiempo del terapeuta 23 . Mohr y cols compararon dos tratamientos psicoterapéuticos administrados telefónicamente a pacientes que sufren de esclerosis múltiple y depresión encontrando que ambos logran reducir la sintomatología depresiva y que la psicoterapia de orientación cognitiva conductual logra resultados específi cos mejores que la psicoterapia focal 24 .…”
Section: Depresiónunclassified